2022
DOI: 10.3390/ma15062181
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Use of Graphene Oxide in Layered Cement Mortar

Abstract: Graphene oxide (GO) has been found to be an attractive nanomaterial to improve the properties of cementitious composites. However, the use of GO in the industry is limited by its high cost. To achieve a higher cost/performance ratio, GO can be strategically applied in certain parts of cementitious composites structure according to the principle of functionally graded materials. In this study, graded distribution of GO in cement mortar was achieved by sequentially casting a fresh GO-incorporated cement layer on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Consequently, the findings of this research demonstrated that the GO incorporation into cement mortar significantly increases its resistance to chloride ion penetration. This is consistent with past studies [23,41]. For the purpose of providing an explanation or a vision of the results obtained, it should be recalled that in the results of gas permeability, related to porosity, in the samples of modified cement mortar with GO, porosity decreased.…”
Section: Chlorides Diffusion In Mortarssupporting
confidence: 91%
“…Consequently, the findings of this research demonstrated that the GO incorporation into cement mortar significantly increases its resistance to chloride ion penetration. This is consistent with past studies [23,41]. For the purpose of providing an explanation or a vision of the results obtained, it should be recalled that in the results of gas permeability, related to porosity, in the samples of modified cement mortar with GO, porosity decreased.…”
Section: Chlorides Diffusion In Mortarssupporting
confidence: 91%
“…GO plays a core role in reducing the porosity of the cement matrix during curing the stage. Small amounts of GO, as little as 0.05%wt, increase compressive strength by 15-33% and flexural strength by 41-59% [35][36][37]. There is currently disagreement between the results reported by various researchers on GO-reinforced cement products because other studies [38,39] have found no improvements or even disadvantages [36,37,40].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GO exhibits a good bond with the cement matrix, further improving the mechanical properties of cement matrix composites. Many scholars have added GO to the cement matrix to study its influence on the properties of cement-based composites [25][26][27][28][29]. Additionally, GO can be prepared from graphite at a lower cost using an improved Hummers' method, laying a good foundation for its widespread use.…”
Section: Introductionmentioning
confidence: 99%